Reinaldo Azevedo em Veja online: um intelectual a serviço da construção do antipetismo - Daltoé, Julius Hericky Hafemann (2017)
We investigated in this work the political performance of Reinaldo Azevedo in VEJA.COM’s portal, online universe of Veja Magazine, between the years of 2009 and 2013. Reinaldo Azevedo became one of the main spokesmen of anti-communism, in the form of Antipetismo, at virtual spaces, producing discourse and giving space for the fomentation of the Antipetista spectrum in Brazilian media. Reinaldo Azevedo started working at VEJA.COM in 2006, between the first and second term of ex-president Luiz Inacio Lula da Silva, under PT’s Government. His years of work at VEJA.COM make Reinaldo Azevedo an emblematic figure of the production of Anticommunist discourse in the Brazilian Reference Press. Thus, our intention with this research was to seek to understand the senses created by Azevedo to compose the Anticommunist discourse in the form of Antipetismo, as well as to evaluate the amplitude of what refers to Antipetista discourse produced by him. We mean, what interests and motivations permeate their production. Working with anticommunist references prior to RA and using Discourse Analysis tools, we investigated the way in which the senses are applied by Reinaldo Azevedo, and we try to understand which are the points of permanence, of the senses previously applied by other producers of this mode of discourse and, in this application, what are the "innovations" produced by Reinaldo Azevedo.